Individuals with Intellectual and Developmental Disabilities Obtaining Washington State Driver’s Licenses - Waehlte, Samantha (My University, 2018)
The purpose of this paper is to is to begin a best practices analysis on how to best create and recommend a structured and effective driving course outline for individuals with intellectual and developmental disabilities in Washington State. Individuals with intellectual and developmental disabilities (IDD) lack the appropriate access and ease to learning how to earn their driver’s license. The problem is not from failing the physical driving test, failing the written knowledge test, or lacking of physical resources such as a practice vehicle, but rather the problem is rooted in not having the option of a class or teacher that can understand their way of learning that would allow for success in learning how to drive and pass the necessary state provided tests. Without a valid driver’s license, individuals with IDD have a smaller pool of options for places of employment, education, health services, and general entertainment. By providing an opportunity for individuals with IDD to properly learn how to drive, it will allow for growth in independence, socialization, critical thinking, and problem solving skills. It’s another piece of documentation that allows individuals with IDD to live their best lives out in the community. Which in turn leads to higher self esteem, greater social circles, and general enjoyment of life through experiences that otherwise would have fallen void.